PENGARUH NILAI KERJA, KECERDASAN EMOSIONAL DAN WORK LIFE BALANCE TERHADAP KOMITMEN KARIR (STUDI KASUS PADA GENERASI Y KOTA SEMARANG) - Baihaqi, Iqbal Baihaqi; Kristanto, Rudi Suryo (ECONBANK: Journal of Economics and Banking, 2020)
The phenomenon that occurs in the field states that almost half the workers surveyed to reach 49% of people say workers have changed their careers or fields of work drastically, it is certainly interesting to do research. This study aims to determine the effect of work value, emotional intelligence, and work life balance on career commitment. The population in this study is the Y generation in the city of Semarang. Non-probability sampling techniques are used to determine the research sample and data collection is done through the distribution of questionnaires to 150 respondents. In this study, the method used is multiple linear regression. From the results of the analysis found that (1) the value of work does not affect career commitment with a significant level of 0.288> 0.05 (2) emotional intelligence affects the career commitment with a significance level of 0.000 <0.05 (3) work life balance does not affect the career commitment with a significance level of 0.814> 0.05. Adjusted R2 value is 0.475, which means 47.5% of variations in Career Commitment can be explained by the independent variables work value, emotional intelligence, and work life balance while the remaining 52.5% career commitment can be explained by other factors.